KORUPSI SEBAGAI BENTUK KEJAHATAN TRANSNASIONAL TERORGANISIR - Dadang Siswanto (Masalah-Masalah Hukum, 2013)
Abstract Many corruption cases, both of which occur in developing countries and in developed countries, often cause difficulties in enforcement. This is because the perpetrators to escape and save the proceeds of corruption to other countries. The establishment of the United Nations Convention against Corruption 2003 is an international effort to tackle the problem. Development of a crime that was once a crime of corruption of national and derived from national law into international crime transnational organized, because of corruption related to economic crime, money laundering as well as the joints can be fragile democracy in a country. International cooperation is needed in order to combat crimes that are transnational corruption. Various forms of cooperation carried out, which include the return of property corruption that is stored in other countries and include several exceptions from the principle of extradition. It is intended to facilitate the enforcement of the law against corruption suspects who fled to other countries, although the country has no extradition requested extradition treaty with the state requested. Keywords : Corruption, international crime, transnational organized crime.   Abstrak   Maraknya kasus korupsi, baik yang terjadi di negara berkembang maupun di negara maju, seringkali menimbulkan kesulitan dalam penegakan hukumnya. Hal ini dikarenakan pelaku melarikan diri dan menyimpan harta hasil korupsinya ke negara lain. Dibentuknya United Nations Convention against Corruption 2003 merupakan suatu upaya internasional untuk menanggulangi persoalan tersebut. Perkembangan kejahatan korupsi yang  dulunya merupakan kejahatan nasional dan bersumber pada hukum nasional menjadi kejahatan Internasional yang bersifat transnasional terorganisir, karena tindak pidana korupsi terkait dengan kejahatan ekonomi, money laundering serta dapat merapuhkan sendi-sendi demokrasi di suatu negara. Kerjasama internasional sangat diperlukan dalam rangka memberantas kejahatan korupsi yang bersifat transnasional tersebut. Berbagai bentuk kerjasama dilakukan, antara lain berupa pengembalian harta korupsi yang disimpan di negara lain dan termasuk beberapa pengecualian dari asas ekstradisi. Hal ini dimaksudkan untuk memudahkan penegakan hukum terhadap tersangka korupsi yang melarikan diri ke negara lain, meskipun negara diminta ekstradisi tidak mempunyai perjanjian ekstradisi dengan negara diminta. Kata Kunci : Korupsi , kejahatan internasional , kejahatan transnasional terorganisir